Estimation of hydraulic parameter (Manning’s roughness coefficient) in mountainous river at middle stage of Hindu Kush Himalaya region - Lamichhane, Suraj; Devkota, Nirajan; Dawadi, Sarita; Tamrakar, Jebin (Journal of Innovations in Engineering Education, 2023)
Manning's roughness coefficient (n) holds significant importance within a hydrodynamic model, yet its value is notably subject to variation, influenced by both time and specific site conditions. Determining the appropriate value for 'n' is a challenging endeavour, particularly in natural watercourses, given the multitude of factors that impact this coefficient. The research unveils findings from a hydraulic model, examining the fluctuation of Manning’s roughness coefficient concerning discharge, thereby influencing the flow depth in the mountainous areas of Nepal situated within the middle stage of the Hindu Kush Himalaya region. This study applied the unsteady flow model HEC-RAS to three comparable reaches in Nepal—the Bagmati River, Kamala River, and Kankai River—to determine the Manning’s coefficient. Through the calibration method, which involves aligning the value to accurately replicate observed data, a suitable Manning’s roughness coefficient "n" was identified. The findings indicate that this coefficient varies notably with reduced discharge and flow depth.